The body and military masculinity in Late Qing and early republican China: the art of governing soldiers - Schillinger, Nicolas (Lexington Books, 2016)
This study examines the cultural effects of China's adoption of a European military model in the late nineteenth and early twentieth centuries. It argues that there was a conceptual reconfiguration of Chinese masculinity and citizenship and focuses on how the body was conceived, shaped by physical fitness and medical practices, and controlled.
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift; Geschichte 1895-1916; Männlichkeit; Militär; China